Somatic component of risk of the development of vegetative-vascular dysfunction at children of the average and advanced school age - Olena Savchuk (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to estimate quantitatively factors of somatic component of risk of the development of vegetative-vascular dysfunction at children of the average and advanced school age. Material & Methods: 569 children of 14-17 years old are examined in order to the existence of somatopathies, violation of posture, level and harmony of physical development, extent of development of adipopexis, functional indicators of health. Influence of somatic factors on risk of developing of vegetative-vascular dysfunction was revealed by means of the correlation analysis. Results: the system of assessment and the integrated indicator of action of somatic factors on risk of the development of vegetative-vascular dysfunction are offered. 6,57% of pupils with the low level of probability of risk of developing of vegetative-vascular dysfunction, 24,25% of pupils with the level below the average, 38,36% of children of 14-17 years old with the average level of probability of risk of developing of vegetative-vascular dysfunction, 24,25% of teenagers with the average level of probability, 6,57% of pupils with the high level of probability of risk of developing of vegetative-vascular dysfunction are revealed. The reliable communications between the low level of functionality on the test of Ruffier and the disharmonious physical development (p<0,001), low indicators of power and respiratory indexes (p<0,05) are established statistically. Conclusions: the children of the group of risk, who need the individual approach at lessons of physical culture, are defined.